2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6853614
|View full text |Cite
|
Sign up to set email alerts
|

Extending coherence time for analysis of modulated random processes

Abstract: In this paper, we relax a commonly-used assumption about a class of nonstationary random processes composed of modulated wide-sense stationary random processes: that the fundamental frequency of the modulator is stationary within the analysis window. To compensate for the relaxation of this assumption, we define the generalized DEMON ("demodulated noise") spectrum representing modulation frequency, which we use to increase the coherence time of such signals. Increased coherence time means longer analysis windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…An alternate theory of locally stationary time series was developed by Dahlhaus [6] (see also [7] for a corresponding stationarity test). In a different context, frequency-modulated stationary signal were considered in [8], [9], and time warping models were analyzed in [10]. In several of these approaches, wavelet, time-frequency and similar representations happen to play a key role for the characterization of nonstationarity.…”
Section: Introductionmentioning
confidence: 99%
“…An alternate theory of locally stationary time series was developed by Dahlhaus [6] (see also [7] for a corresponding stationarity test). In a different context, frequency-modulated stationary signal were considered in [8], [9], and time warping models were analyzed in [10]. In several of these approaches, wavelet, time-frequency and similar representations happen to play a key role for the characterization of nonstationarity.…”
Section: Introductionmentioning
confidence: 99%
“…Degottex and Stylianou [18] proposed another analysis/synthesis scheme for speech using an adaptive harmonic model that they claim is more flexible than the fan-chirp, as it allows nonlinear frequency trajectories. Wisdom et al showed that the fan-chirp transform can be used to build optimal detectors for nonstationary harmonics [19] and harmonically-modulated stationary processes with timevarying modulation frequency [20]. A preliminary version of this algorithm appeared in our REVERB challenge workshop paper [8].…”
Section: Introductionmentioning
confidence: 99%